2017
DOI: 10.1016/j.cellsig.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal motif of human neuropeptide Y4 receptor determines internalization and arrestin recruitment

Abstract: The human neuropeptide Y4 receptor is a rhodopsin-like G protein-coupled receptor (GPCR), which contributes to anorexigenic signals. Thus, this receptor is a highly interesting target for metabolic diseases. As GPCR internalization and trafficking affect receptor signaling and vice versa, we aimed to investigate the molecular mechanism of hY4R desensitization and endocytosis. The role of distinct segments of the hY4R carboxyl terminus was investigated by fluorescence microscopy, binding assays, inositol turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…As previous studies have already shown the importance of the arrestin3 (arr3) pathway for Y 4 R signaling, we investigated the activity of VU0637120 on arr3 recruitment as an alternative pathway to G protein signaling. PP-induced arr3 recruitment to the Y 4 R was analyzed in kinetic experiments by detecting arr3 recruitment to the Y 4 R constantly over 30 min (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have already shown the importance of the arrestin3 (arr3) pathway for Y 4 R signaling, we investigated the activity of VU0637120 on arr3 recruitment as an alternative pathway to G protein signaling. PP-induced arr3 recruitment to the Y 4 R was analyzed in kinetic experiments by detecting arr3 recruitment to the Y 4 R constantly over 30 min (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In the arr3 recruitment studies, the Y 4 R was C-terminally tagged to Renilla luciferase 8 (Rluc8) and cloned in a pcDNA3 vector. Arr3 was N-terminally fused to venus fluorescent protein and cloned in a pcDNA3 plasmid. , The sequence of all constructs was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…For example, all 19 possible amino acid substitutions at Ala293 of the α1 adrenergic receptor result in constitutive G protein activity 50 , while a single serine to alanine mutation in the C-terminus of the apelin receptor (APJ) inactivates GRK phosphorylation and blunts βarrestin signaling 51 . In the C-terminus of neuropeptide Y 4 receptor, mutation of glutamic acid, serine or threonine residues disrupts agonist induced recruitment of βarrestin-2 and receptor endocytosis 52 . The chemokine receptor CXCR7 was initially classified as a non-signaling ‘decoy’ receptor, although it was later shown that CXCR7 engages ligand dependent βarrestin recruitment and signaling while lacking appreciable G-protein signaling 53 .…”
Section: Ligand Bias Receptor Bias and System Biasmentioning
confidence: 99%
“…A number of naturally occurring mutations were found to alter signaling pathways of GPCRs ( 52 ). For example, substitution of a TM6 residue of α1-adrenergic receptor led to constitutive G protein activity ( 53 ); a leucine-to-glutamine mutation in the TM3 helix of cysteinyl-leukotriene receptor 2 strongly drove G q/11 signaling ( 54 ); and mutations in the C terminus of several class A GPCRs, including apelin receptor and neuropeptide Y4 receptor, diminished β-arrestin recruitments ( 55 , 56 ). Although many genetic variations of GPCRs have been detected ( 34 ), the mechanisms governing signal bias are poorly understood.…”
Section: Discussionmentioning
confidence: 99%